2023
DOI: 10.1111/ssqu.13304
|View full text |Cite
|
Sign up to set email alerts
|

The stability of personal traits and preferences in times of the Corona pandemic: Evidence from Germany

Abstract: Based on panel data on around 5500 German households, this article analyzes whether the experience of financial losses due to the Corona pandemic has affected three kinds of personal traits and preferences: the willingness to take risks, patience, and the locus of control (LOC). Our empirical results indicate that patience and the LOC remain unchanged by the experience of pandemic‐related financial losses, whereas we find a negative effect of severe financial losses on risk‐taking, contrasting with the traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…They find that these changes are not related to age, health outcomes, or labour market outcomes. More recently, Frondel et al (2023) found that experiencing financial losses from the coronavirus pandemic also does not change locus of control.…”
Section: Establishing the Hypothesismentioning
confidence: 99%
“…They find that these changes are not related to age, health outcomes, or labour market outcomes. More recently, Frondel et al (2023) found that experiencing financial losses from the coronavirus pandemic also does not change locus of control.…”
Section: Establishing the Hypothesismentioning
confidence: 99%